A potential role of fatty acid binding protein 4 in the pathophysiology of autism spectrum disorder. Issue 2 (10th September 2020) - Maekawa, Motoko; Ohnishi, Tetsuo; Toyoshima, Manabu; Shimamoto-Mitsuyama, Chie; Hamazaki, Kei; Balan, Shabeesh; Wada, Yuina; Esaki, Kayoko; Takagai, Shu; Tsuchiya, Kenji J; Nakamura, Kazuhiko; Iwata, Yasuhide; et al.
Abstract: Autism spectrum disorder is a neurodevelopmental disorder characterized by difficulties in social communication and interaction, as well as repetitive and characteristic patterns of behaviour. Although the pathogenesis of autism spectrum disorder is unknown, being overweight or obesity during infancy and low weight at birth are known as risks, suggesting a metabolic aspect. In this study, we investigated adipose tissue development as a pathophysiological factor of autism spectrum disorder by examining the serum levels of adipokines and other metabolic markers in autism spectrum disorder children ( n  = 123) and typically developing children ( n  = 92) at 4–12 years of age. Among multiple measures exhibiting age-dependent trajectories, the leptin levels displayed different trajectory patterns between autism spectrum disorder and typically developing children, supporting an adipose tissue-dependent mechanism of autism spectrum disorder. Of particular interest, the levels of fatty acid binding protein 4 (FABP4) were significantly lower in autism spectrum disorder children than in typically developing subjects, at preschool age (4–6 years old: n  = 21 for autism spectrum disorder and n  = 26 for typically developing). The receiver operating characteristic curve analysis discriminated autism spectrum disorder children from typically developing children with a sensitivity of 94.4% and a specificity of 75.0%. We re-sequenced the exons of the FABP4 gene in a Japanese cohort comprising 659 autism spectrum disorder and 1000 control samples, and identified two rare functional variants in the autism spectrum disorder group. The Trp98Stop, one of the two variants, was transmitted to the proband from his mother with a history of depression. The disruption of the Fabp4 gene in mice evoked autism spectrum disorder-like behavioural phenotypes and increased spine density on apical dendrites of pyramidal neurons, which has been observed in the postmortem brains of autism spectrum disorder subjects. The Fabp4 knockout mice had an altered fatty acid composition in the cortex. Collectively, these results suggest that an 'adipo-brain axis' may underlie the pathophysiology of autism spectrum disorder, with FABP4 as a potential molecule for use as a biomarker. Abstract : We discovered lower circulating fatty acid binding protein 4 (FABP4), mainly secreted by the adipose tissue, in children with autism spectrum disorder, and identified functional FABP4 variants in the autism spectrum disorder group. Furthermore, Fabp4 knock-out mice displayed autism spectrum disorder-relevant phenotypes. We propose that the 'adipo-brain axis' may underlie the pathophysiology of autism spectrum disorder. Graphical Abstract: